The relationship of pain severity with anxiety, depression, somatic symptoms, personality, and alexithymia in the early period after total knee arthroplasty - Turan, Çetin; Küçükalp, Abdullah (The European Research Journal, 2023)
Objectives: This study aims to investigate the relationship between pain severity in the early postoperative period and preoperative psychometric factors in individuals undergoing total knee arthroplasty (TKA). Methods: This research was designed as a cross-sectional and descriptive study. Fifty participants undergoing TKA were inpatients at a private hospital’s Orthopedics and Traumatology Clinic were included in the study. The same anesthesia protocol (spinal anesthesia) and the same surgical technique were performed on all patients. In data collection, Visual Analogue Scale (VAS), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Somatic Amplification Scale (SAS), Toronto Alexithymia Scale (TAS), Eysenck Personality Questionnaire Revised-Abbreviated (EPQR-A), and Sociodemographic Data Form were used. Results:The mean age of the participants in the study was 64.80 ± 8.70 years, and 45 of the cases (90.0%) were women. Considering the Single Factor ANOVA Analysis, only psychoticism subscale scores were observed to be statistically significant in the change in VAS-Static scores. When all psychometric properties were controlled, the significant change in VAS-Dynamic scores was shown to continue at low effect. Conclusions: According to these findings, the psychoticism dimension was concluded to be more associated with an antisocial personality disorder or aggressive patients, and the high level of pain in these patients may be related to low levels of serotonin and cortisol from a neurobiological point of view.